Chapter 5.35 The Profession of Research Management and Administration in the Netherlands - Anna Groeninx van Zoelen; Edwin Kanters (Emerald Publishing Limited, 2023)
In this chapter, we show the development of the Dutch research funding support during the past 40 years. As well as the evolution of the research funding ecosystem in science and innovation. We show where Research Managers and Administrators (RMAs) started, how they developed and which developments in the research and innovation policy coincides with those origins and developments. Especially showing the exponential development of RMA in the past 10 years. The past and current situation in the Netherlands is distinctive due to the history behind the professionalisation of the profession.
10.1108/978-1-80382-701-820231069; 10.1108/978-1-80382-701-820231069; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262